Análisis del comportamiento mecánico de prótesis de pie más usada en Colombia mediante la técnica de elementos finitos. (2012)
In the development of the gait analysis of prosthesis users, the importance that this has for their daily life can be found, given that by powering any motor function of the human body these systems replace these shortcomings, and different important needs can be found for each user since they are each different in terms of technical requirements. The origin of this analysis lies in the problems that the use of this type of systems causes to patients, pathologies that occur in the spine and generation of lameness present problems in the hip joint, throughout history they have been performed these analyzes on different types of patients to improve their mobility, since it became a necessity for users, in this way different types of joints have been developed and experimenting with different materials to improve and look more like the human body.